ROR1 and ROR2 in Human Malignancies: Potentials for Targeted Therapy - Rebagay, Guilly; Yan, Su; Liu, Cheng; Cheung, Nai-Kong (Frontiers in Oncology, 2012)
Targeted therapies require cellular protein expression that meets specific requirements that will maximize effectiveness, minimize off-target toxicities, and provide an opportunity for a therapeutic effect. The receptor tyrosine kinase-like orphan receptors (ROR) are possible targets for therapy that may meet such requirements. RORs are transmembrane proteins that are part of the receptor tyrosine kinase (RTK) family. The RORs have been shown to play a role in tumor-like behavior, such as cell migration and cell invasiveness and are normally not expressed in normal adult tissue. As part of the large effort in target discovery, ROR proteins have recently been found to be expressed in human cancers. Their unique expression profiles may provide a novel class of therapeutic targets for small molecules against the kinase or for antibody-based therapies against these receptors. Being restricted on tumor cells and not on most normal tissues, RORs are excellent targets for the treatment of minimal residual disease, the final hurdle in the curative approach to many cancers, including solid tumors such as neuroblastoma. In this review, we summarize the biology of RORs as they relate to human cancer, and highlight the therapeutic approaches directed toward them.